A pentatomomorpha-specific salivary protein activates plant immunity and is critical for insect feeding - Biao Hu; Xiuli Feng; Manru Xu; Yue Huang; Chunyun Guo; Ruikun Yuan; Yiyuan Li; Zhongyan Wei; Jianping Chen; Zongtao Sun (Proceedings of the National Academy of Sciences, 2025)
The stinkbug Riptortus pedestris , notorious for inducing soybean staygreen-like syndrome, employs a range of salivary proteins to manipulate the host plant for its benefit. Here, we show that RpSP1, a salivary protein specific to Pentatomomorpha, triggers plant defense responses in multiple plant species. RpSP1 interacts with and stabilizes a HSP40 family protein GmSPIP1 and is dependent on GmSPIP1 to induce cell death. We show that a critical 22-amino acid peptide within RpSP1 acts as an intracellular insect-derived elicitor. Furthermore, RpSP1 enhances insect-feeding efficiency. The dual functionality of RpSP1 is highlighted by the significant reduction of soybean staygreen-like syndrome following its overexpression in soybean plants or knockdown in insects. Our findings elucidate the complex molecular interactions between plants and herbivores, positioning RpSP1 as a crucial target for developing advanced pest management strategies with broad implications for agricultural biology.